Gender matters : feminist linguistic analysis - Mills, Sara, 1954- (Equinox Pub., 2012)
Gender Matters presents a feminist linguistic analysis of texts - literature, media and lyrics - and conversation. It explores how gender relates to and shapes our understanding of sexism, reading and writing, politeness and public speaking. The essays in the book examine a range of questions: why is it necessary for feminists to analyse or comment on sexism when sexism is widely regarded as an anachronistic concern? How can feminists describe the effect of gender on the experience of literature? Why are women considered more capable of private rather than public speech? What is the relation b.